Analisis Nilai Output Home Industri Kulit Buaya di Kota Merauke - Marthen A.I. Nahumury (Universitas Musamus,Merauke,Papua, 2022)
Merauke is one of the cities that produces handicrafts made from crocodile skin, so many people use this crocodile skin as souvenirs when visiting the city of Merauke. The purpose of this study was to see the level of influence of capital on the output value of the Crocodile Skin home industry in Merauke City. This research is a quantitative research. The type of data in this study primary data is data collected through the distribution of questionnaires. The population in this study were crocodile skin craftsmen in Merauke City, totaling 58 crocodile skin craftsmen in Merauke City. The sampling method used is saturated sampling (census), the samples used in this study were 58 crocodile skin craftsmen. The results of this study indicate that capital has a positive and significant effect on the output value of the crocodile skin home industry in the city of Merauke. Labor has a positive and significant effect on the output value of the crocodile skin home industry in the city of Merauke. Capital, and labor together affect the output value of the crocodile skin home industry